Creep behavior of V-notched components - P. Gallo; S.M.J. Razavi; M. Peron; J. Torgersen; F. Berto (Fracture and Structural Integrity)
Geometrical discontinues such as notches play a significant rule in structural integrity of the components, especially when the component is subjected to very severe conditions, such as the high temperature fatigue or creep. In this paper, a generalized form of the existing notch tip creep stressstrain analysis method developed by Nuñez and Glinka, is developed and extended to a wide variety of blunt V-notches. Assuming the generalized Lazzarin-Tovo solution that allows a unified approach to the evaluation of linear elastic stress fields in the vicinity of both cracks and notches is the key in getting the extension to blunt V-notches. Numerous cases have been analysed and the stress fields obtained according to the proposed method were compared with proper finite element data, showing a very good agreement.